A terceira presidência rotativa de Angola na SADC - Almeida, E. C. (Figuras & Negócios, 2024)
Abstract: Since August 17th, during the 43rd Summit of Heads of State and Government of the Southern African Region held in Luanda, under the theme "Human and Financial Capital: The Main Drivers of Sustainable Industrialization in the SADC Region," Angola has once again taken on the annual rotating presidency of the Southern African Development Community (SADC) for a period of one year, until August 2024. An analysis of the presidency and the statutory parameters of SADC reveals how it has managed to include other more global parameters that are integral to the African Union, such as the Rapid Intervention Forces (or African Standby Forces).